2013
DOI: 10.1080/10871209.2012.686082
|View full text |Cite
|
Sign up to set email alerts
|

Grouse Hunting Regulations and Hunter Typologies in Norway

Abstract: Game management relies on satisfied hunters. Satisfaction determinants are, however, seldom uniform across the whole hunter segment and may therefore be difficult to accommodate.Latent class analysis (LCA) is a probabilistic model-based approach to categorizing hunter typologies by, for example, their attitudes and preferences. We applied LCA to large-scale survey data relating to grouse hunting regulations in Norway (3,293 respondents). We identified three typologies with regard to importance of bag size (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
3
18
0
1
Order By: Relevance
“…Both for, hunters' daily effort, which could reduce their hunting success, and hunters will to return to the area the next year. Contradictory, Wam et al (2013) suggested that most grouse hunters show a quite high crowding tolerance. The result may imply that the recreational carrying capacity was reached (Shelby and Heberlein 1986), and may be the reason for the harvest management with an upper limit of three accumulated hunter days per km 2 in all management areas was not put into action during our study period.…”
Section: Discussionmentioning
confidence: 99%
“…Both for, hunters' daily effort, which could reduce their hunting success, and hunters will to return to the area the next year. Contradictory, Wam et al (2013) suggested that most grouse hunters show a quite high crowding tolerance. The result may imply that the recreational carrying capacity was reached (Shelby and Heberlein 1986), and may be the reason for the harvest management with an upper limit of three accumulated hunter days per km 2 in all management areas was not put into action during our study period.…”
Section: Discussionmentioning
confidence: 99%
“…Estos sistemas coinciden con los descritos para otras aves de caza del norte de Europa (p.ej. Wam, Andersen y Pedersen, 2013). No todos estos mecanismos tienen la misma eficacia para regular la extracción total y, en última instancia, la sostenibilidad de la caza.…”
Section: Presión Cinegéticaunclassified
“…Th ere are basically two ways to adjust harvest rates: 1) to limit the total number of ptarmigan harvested (total bag size), or 2) reduce the total eff ort by 2.1) reducing the length of hunting season, and/or 2.2) reducing the number of hunters (Wam et al 2013). Combinations of these three harvest principles are also possible.…”
mentioning
confidence: 98%